2008
DOI: 10.1007/s11325-008-0232-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a portable recording device (ApneaLink™) for case selection of obstructive sleep apnea

Abstract: The ApneaLink is an ambulatory sleep monitor that can detect OSA and/or hypopnea with acceptable reliability. The screening and diagnostic capability needs to be verified by further evaluation and manual scoring of the ApneaLink. It could be a better choice than traditional oximetry in terms of recording respiratory events, although severity may be under- or overestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 22 publications
4
86
1
Order By: Relevance
“…Some previous studies 18,19,27,28 have validated this PM in the laboratory (i.e., concurrent with PSG) and reported good sensitivity (80% to 100%) to rule in OSA (AHI ≥ 5 events/h) but variable specificity (50% to 100%), with LR+ values ranging from 1.9 to infinity. Our study showed high diagnostic accuracy to rule in OSA with specificity 100% and LR+ infinity on the simultaneous night assessment.…”
Section: -11mentioning
confidence: 85%
See 3 more Smart Citations
“…Some previous studies 18,19,27,28 have validated this PM in the laboratory (i.e., concurrent with PSG) and reported good sensitivity (80% to 100%) to rule in OSA (AHI ≥ 5 events/h) but variable specificity (50% to 100%), with LR+ values ranging from 1.9 to infinity. Our study showed high diagnostic accuracy to rule in OSA with specificity 100% and LR+ infinity on the simultaneous night assessment.…”
Section: -11mentioning
confidence: 85%
“…The subject took the equipment home, wore it during a "usual" night's sleep and returned it by post. During simultaneous PM and PSG (P2), the nasal pressure signal was delivered to both sleep systems using a Y-piece in the nasal catheter, a methodology validated in previous studies, [16][17][18][19] and the subject wore separate oximetry finger probes for the PM device and PSG. At the conclusion of the PSG all subjects were given a PM device and instructed about its correct use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This sample selection is not representative of the typical age profile of OSA sufferers. Most previous studies that validated AL in OSA patients included younger middle-aged patients [5,6,10,11]. In addition, the study recruited Caucasians and Asians.…”
Section: A Paper By Mcevoy Et Al Recently Appeared In the Newmentioning
confidence: 99%